Health Tracking Household Survey, 2010 (United States) ([Verlag nicht ermittelbar], 2012)
This is the second survey in the Health Tracking Household Survey (HTHS) series, the successor to the Community Tracking Study (CTS) Household Surveys. The CTS Household Surveys were conducted in 1996-1997 (ICPSR 2524), 1998-1999 (ICPSR 3199), 2000-2001 (ICPSR 3764), and 2003 (ICPSR 4216), and the first HTHS survey was conducted in 2007 (ICPSR 26001). Although the HTHS questionnaires are similar to the CTS Household Survey questionnaires, the HTHS sampling design does not have the community focus intrinsic to CTS. Whereas the CTS design focused on 60 nationally representative communities with sample sizes large enough to draw conclusions about health system change in 12 communities, the HTHS design is a national sample not aimed at measuring change within communities. Hence, "Community" was dropped from the study title. Like the previous surveys, this survey collected information on health insurance coverage, use of health services, health expenses, satisfaction with health care and physician choice, unmet health care needs, usual source of care and patient trust, health status, and adult chronic conditions. In addition, the survey inquired about perceptions of care delivery and quality, problems with paying medical bills, use of in-store retail and onsite workplace health clinics, patient engagement with health care, sources of health information, and shopping for health care. At the beginning of the interview, a household informant provided information about the composition of the household which was used to group the household members into family insurance units (FIU). Each FIU comprised an adult household member, his or her spouse or domestic partner (same sex and other unmarried partners), if any, and any dependent children 0-17 years of age or 18-22 years of age if a full-time student (even if living outside the household). In each FIU in the household, a FIU informant provided information on insurance coverage, health care use, usual source of care, and general health status of all FIU members. This informant also provided information on family income as well as employment, earnings, employer-offered insurance plans, and race/ethnicity for all adult FIU members. Moreover, every adult in each FIU (including the FIU informant) responded through a self-response module to questions that could not be answered reliably by proxy respondents, such as questions about unmet needs, usual source of care, assessments of the quality of care, consumer engagement, satisfaction with physician choice, use of health information, health care shopping, and detailed health questions. The FIU informants responded on behalf of children regarding unmet needs, satisfaction with physician choice, and use of health care information.